Сюжетно-тематична різьба у творчості Миколи Грепиняка (до сімдесятип’ятиріччя від дня народження) - Білий, В. (Народна творчість та етнографія, 2008)
The article represents life and the creative way of the modern artistic wooden hand-made goods master Hrepynyak Mykola Ivanovych who comes from the village Verkhni Bereziv of Kosiv Region. He is one of those artists who has made a great contribution to the development of the artistic carving both as a teacher and an innovator as for the combination of the traditional Hutsul design motifs together with the plot compositions in the carving and incrustation technigues.